PERAN KEPALA SEKOLAH SEBAGAI MANAJER PENDIDIKAN DALAM MENGOPTIMALKAN KINERJA MENGAJAR GURU DI DAERAH KHUSUS - Sukma Puri Bektiyastri; Mustiningsih Mustiningsih; Sultoni Sultoni; Desi Eri Kusumaningrum; Sukma Puri Bektiyastri; Mustiningsih Mustiningsih; Sultoni Sultoni (Universitas Negeri Malang, 2024)
Abstract This study aims to describe the role of the school principal as an education manager in optimizing the teacher’s teaching performance in a particular region. The researcher uses qualitative methods, namely case study type. The results are: (1) the school principal have roles in regulating the facilities and infrastructures in school by making plans and listing priorities based on BOS technical guidelines; (2) the principal have roles in managing the classroom by monitoring, providing direction, supervision, and providing teachers with training activities; (3) the school principal have roles in developing a good working relationship by accustoming active communication, involving the nearby community in school activities, and creating a school program namely “Ayo Sekolah”; lastly (4) the school principal have roles in reinforcing teachers by giving reward to the teachers. The reward is by supporting teachers in developing their teaching performance, career, potential, and getting a better assessment system for teachers. The school principal can improve the teachers’ teaching performance by providing ratings to teachers and implementing reprimands and punishments for teachers and students.